The Use of the Maternal and Child Health (KIA) Book as a Medium to Improve Mothers’ Knowledge and Skills in Toddler Development Stimulation: A Community Service in Wage Village, Sidoarjo - Dewi, Uke Maharani; Novianti, Hinda; Munjidah, Annif; Masita, Elly Dwi; Choirotussanijjah, Choirotussanijjah (Amalee: Indonesian Journal of Community Research and Engagement, 2025)
The main obstacle in toddler development monitoring is the limited knowledge of mothers regarding stimulation and early detection. Previous community services in several regions generally focused on counseling at posyandu or health facilities. However, these efforts often emphasized knowledge transfer only, without sufficient emphasis on hands-on practice or continuous assistance, resulting in limited impact on mothers’ actual skills. This gap highlights the need for community-based programs that increase knowledge and strengthen practical skills through direct mentoring. This community service was implemented in Wage Village, Sidoarjo Regency, involving 24 mothers of toddlers. The intervention consisted of training sessions using lectures, demonstrations, and guided practice with the Maternal and Child Health (KIA) book as the primary tool. Pre-test and post-test evaluations were conducted using questionnaires on knowledge and skills. The results showed a significant increase, with 83.3% of mothers reaching the high category in knowledge and 91.7% in skills after the training. These findings indicate that practice-based training with intensive assistance effectively empowers mothers. Continuous mentoring at posyandu is recommended for future programs to ensure sustainability and broader community impact.